Application of a novel diamond detector for commissioning of FLASH radiotherapy electron beams. Issue 8 (16th June 2022) - Verona Rinati, Gianluca; Felici, Giuseppe; Galante, Federica; Gasparini, Alessia; Kranzer, Rafael; Mariani, Giulia; Pacitti, Matteo; Prestopino, Giuseppe; Schüller, Andreas; Vanreusel, Verdi; Verellen, Dirk; Verona, Claudio; et al.
Abstract: Purpose: A diamond detector prototype was recently proposed by Marinelli et al. (Medical Physics 2022, https://doi.org/10.1002/mp.15473 ) for applications in ultrahigh‐dose‐per‐pulse (UH‐DPP) and ultrahigh‐dose‐rate (UH‐DR) beams, as used in FLASH radiotherapy (FLASH‐RT). In the present study, such so‐called flashDiamond (fD) was investigated from the dosimetric point of view, under pulsed electron beam irradiation. It was then used for the commissioning of an ElectronFlash linac (SIT S.p.A., Italy) both in conventional and UH‐DPP modalities. Methods: Detector calibration was performed in reference conditions, under 60 Co and electron beam irradiation. Its response linearity was investigated in UH‐DPP conditions. For this purpose, the DPP was varied in the 1.2–11.9 Gy range, by changing either the beam applicator or the pulse duration from 1 to 4 μs. Dosimetric validation of the fD detector prototype was then performed in conventional modality, by measuring percentage depth dose (PDD) curves, beam profiles, and output factors (OFs). All such measurements were carried out in a motorized water phantom. The obtained results were compared with the ones from commercially available dosimeters, namely, a microDiamond, an Advanced Markus ionization chamber, a silicon diode detector, and EBT‐XD GAFchromic films. Finally, the fD detector was used to fully characterize the 7 and 9 MeV UH‐DPP electron beams delivered by the ElectronFlash linac. In particular, PDDs, beam profiles, and OFs were measured, for both energies and all the applicators, and compared with the ones from EBT‐XD films irradiated in the same experimental conditions. Results: The fD calibration coefficient resulted to be independent from the investigated beam qualities. The detector response was found to be linear in the whole investigated DPP range. A very good agreement was observed among PDDs, beam profiles, and OFs measured by the fD prototype and reference detectors, both in conventional and UH‐DPP irradiation modalities. Conclusions: The fD detector prototype was validated from the dosimetric point of view against several commercial dosimeters in conventional beams. It was proved to be suitable in UH‐DPP and UH‐DR conditions, for which no other commercial real‐time active detector is available to date. It was shown to be a very useful tool to perform fast and reproducible beam characterizations in standard clinical motorized water phantom setups. All of the previously mentioned demonstrate the suitability of the proposed detector for the commissioning of UH‐DR linac beams for preclinical FLASH‐RT applications.